2023
DOI: 10.3389/fspas.2023.1217737
|View full text |Cite
|
Sign up to set email alerts
|

Ionosphere-thermosphere coupling via global-scale waves: new insights from two-years of concurrent in situ and remotely-sensed satellite observations

Federico Gasperini,
Brian J. Harding,
Geoffrey Crowley
et al.

Abstract: Growing evidence indicates that a selected group of global-scale waves from the lower atmosphere constitute a significant source of ionosphere-thermosphere (IT, 100–600 km) variability. Due to the geometry of the magnetic field lines, this IT coupling occurs mainly at low latitudes (< 30°) and is driven by waves originating in the tropical troposphere such as the diurnal eastward propagating tide with zonal wave number s = −3 (DE3) and the quasi-3-day ultra-fast Kelvin wave with s = −1 (UFKW1). In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Previous studies (e.g., Chang et al, 2011;Forbes & Roble, 1990;Forbes et al, 2021;Gasperini et al, 2015Gasperini et al, , 2021Gasperini et al, , 2023Gu et Oberheide et al, 2015;Yiğit et al, 2016) demonstrated that upward propagating waves of tropospheric origin can have remarkable influences on interaction and coupling between large-scale wave structures in the low-latitude IT system. CTMT density (Oberheide et al, 2009) and temperature (Forbes et al, 2014) tides have already been extensively tested and validated with Challenging Minisatellite Payload (CHAMP) satellite data.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies (e.g., Chang et al, 2011;Forbes & Roble, 1990;Forbes et al, 2021;Gasperini et al, 2015Gasperini et al, , 2021Gasperini et al, , 2023Gu et Oberheide et al, 2015;Yiğit et al, 2016) demonstrated that upward propagating waves of tropospheric origin can have remarkable influences on interaction and coupling between large-scale wave structures in the low-latitude IT system. CTMT density (Oberheide et al, 2009) and temperature (Forbes et al, 2014) tides have already been extensively tested and validated with Challenging Minisatellite Payload (CHAMP) satellite data.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…The aggregate effect of these tidal wave components likely forms the antisymmetric structure of WN1 (Figure 8) which can also be seen in the WN1 structures of electron density in DMSP‐18 (Figure 4) and the neutral density in Swarm‐C (Figure 5) data. DW2 and D0 have upper thermospheric sources and are generated in situ by a nonlinear interaction of DW1/SPW1 type (Oberheide et al., 2011a) whereas DW1 has a strong dependency on solar activity and season/latitude (Gasperini et al., 2023). SE2 can propagate from the troposphere.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 3 more Smart Citations